Performance analysis of a novel solar assisted air source heat pump - Sezen, Kutbay (International Conference on Applied Engineering and Natural Sciences, 2023)
Solar assisted heat pumps (SAHPs) are energy-efficient and environmentally friendly heating systems that utilize solar energy in different configurations. In this study, the potential benefits of heating the evaporator inlet air using solar energy as a new method were investigated using a developed correlation. The study focused on a 4 kW air conditioner that achieved a COP value of 4.17 for heating with an indoor temperature of 20C and an outdoor temperature of 7C. The aim was to determine how the COP value, evaporator inlet air temperature, and total power consumption changed based on the amount of solar energy transferred when the system was supported using the mentioned method. It was observed that a solar support of 5000 W increased the COP value of the SAHP from 4.17 to 4.99.